A Overlapping Carrier Based SPWM for a 5-Level Cascaded H-bridge Multilevel Inverter - Kureve D. Teryima; Goshwe Y. Nentawe; Agbo O. David (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper proposes a switching control for a cascaded H-bridge inverter structure with reduced switches which is used to improve the THD performance of a single phase five level CHB MLI. The multi level inverter is simulated for the conventional carrier overlapping APOD and the proposed carrier overlapping APOD Pulse Width Modulation (PWM) switching control technique. The total harmonic distortion (THD) of the output voltages are observed for both PWM control techniques. The performance of the symmetric CHB MLI is simulated using MATLAB-SIMULINK. It is observed that the proposed carrier overlapping APODPWM provides output with relatively low THD as compared to the conventional carrier overlapping APODPWM.